DIGITAL WELL-BEING REMAJA: PSIKOEDUKASI UNTUK MENJAGA KESEIMBANGAN ANTARA DUNIA NYATA DAN DUNIA MAYA - Ananda Saadatul Maulidia; Devi Marganing Tyas; Juan Berlianto Wahyudi (Jurnal Pengabdian Masyarakat Khatulistiwa, 2025)
ABSTRACTThe Digital Well-Being Psychoeducation Program was implemented at SMKN 2 Cikarang Barat to enhance students’ understanding and awareness of healthy, balanced, and responsible technology use. The program involved 40 students from grades X and XI, aged 15 to 18 years old. The learning materials covered key topics including the digital world and its psychological impacts, strategies for managing screen time, digital literacy, and the development of essential psychological skills such as self-esteem and assertive communication. The sessions were designed to be interactive and reflective, integrating discussions, educational games, and contextual activities that resonated with students’ everyday digital experiences. Results from the pre-test and post-test demonstrated a notable increase in comprehension, with the proportion of students classified as having “good knowledge” rising from 27.5% to 62.5%. Beyond cognitive improvement, students’ reflective feedback indicated positive growth in digital awareness and self-regulation, such as better time management, more critical evaluation of online information, and improved balance between online and offline activities. As part of the program’s sustainability efforts, a follow-up initiative was developed through the creation of a Digital Well-Being school wall magazine and the use of the school’s official social media platforms to showcase student-produced educational content. These initiatives aim to nurture a lasting culture of digital wellness and literacy within the school community. Overall, the findings suggest that psychoeducation serves not only to strengthen digital literacy but also to foster a reflective, empathetic, and sustainable approach to digital well-being among adolescents.Keywords: Psychoeducation, Digital Well-Being, Digital Literacy, Adolescents ABSTRAKProgram Psikoedukasi Digital Well-Being dilaksanakan di SMKN 2 Cikarang Barat untuk meningkatkan kesadaran dan pemahaman siswa mengenai penggunaan teknologi yang sehat, seimbang, dan bertanggung jawab. Kegiatan ini melibatkan 40 siswa kelas X dan XI berusia 15–18 tahun, dengan materi meliputi dampak psikologis kehidupan digital, pengelolaan waktu layar, literasi digital, serta keterampilan pribadi seperti harga diri dan komunikasi asertif. Kegiatan dirancang secara interaktif dan reflektif melalui diskusi, permainan, dan aktivitas yang relevan dengan kehidupan digital siswa sehari-hari. Hasil pre-test dan post-test menunjukkan peningkatan pemahaman yang signifikan, dengan kategori “pengetahuan baik” meningkat dari 27,5% menjadi 62,5%. Siswa juga melaporkan peningkatan kemampuan dalam mengatur waktu, berpikir kritis terhadap informasi daring, serta menjaga keseimbangan antara aktivitas online dan offline. Sebagai upaya keberlanjutan, siswa membuat mading Digital Well-Being dan membagikan konten edukatif melalui mediaKata Kunci: Psikoedukasi, Kesejahteraan Digital, Literasi Digital, Remaja